Mixed Signals Among Panel Cointegration Tests - Christoph Hanck (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2006)
Time series cointegration tests, even in the presence of large sample sizes, often yield conflicting conclusions (?mixed signals?) as measured by, inter alia, a low correlation of empirical p-values [see Gregory et al., 2004, Journal of Applied Econometrics]. Using their methodology, we present evidence suggesting that the problem of mixed signals persists for popular panel cointegration tests. As expected, there is weaker correlation between residual and system-based tests than between tests of the same group.
Keywords: 519; Panel cointegration tests; Monte Carlo comparison